Some Sequence Spaces and Their Matrix Transformations - Ray, Suresh (Kathmandu University Journal of Science, Engineering and Technology, 2014)
The most general linear operator to transform from a new sequence space into another sequence space is actually given by an infinite matrix. In the present paper, we represent some sequence spaces and provide the characterization of (Sl∞ (p), l∞) and (Sl∞ (p), cs).